Where the Red Fern Grows: with Connections - Wilson Rawls (U.S.A,NY,London Holt, Rinehart, and Winston, 1961)
This classic about a 10-year-old boy growing up in the Ozark mountains with his inseparable pair of coonhounds will warm the hearts of young and old alike.
Keywords: Action / Adventure + Classic, Animals, Historical Fiction -- Action / Adventure + Classic, Animals, Historical Fiction